AN APPROACH TO OPTIMIZATION OF A THREE PHASE CATALYTIC SLURRY REACTOR BY EVOLUTIONARY OPTIMIZATION WITH GENETIC ALGORITHMS - Melo, D.N.C.; de Toledo, E.C. Vasco; Mariano, A.P.; Santos, M.M.; Filho, R. Maciel (IFAC Proceedings Volumes, 2007)
The present work introduces an investigation study about the optimization of a three-phase catalytic slurry reactor with phase changes. The study aims to determine the optimal operational conditions and, in a second stage, advanced control algorithms will be evaluated. A dynamic heterogeneous mathematical model formulation was used and genetic algorithms (GA) were employed to solve a nonlinear quadratic problem subject to bounds on the variables. The solutions obtained using the genetic algorithms gave suitable results to optimize the process by adjusting parameters as the reactor feed temperature and the flow rate of one of the reactants. It was possible to reach operation conditions that ensured a suitable profit and an acceptable compromise with the specifications of the desired product.